Systematic Child Talks in Early Childhood Education-A Method for Sustainability - Ingrid Engdahl; Ingrid Pramling Samuelsson; Eva Ärlemalm-Hagsér (MDPI AG, 2023)
One of a preschool teacher's most important competencies is to be able to talk with children and to invite them to share their ideas, knowledge, and experiences. This skill is of utmost importance within Early Childhood Education for sustainability. The aim of this article is to show various ways in which preschool teachers carry out systematic talks with children. Data come from a large Swedish development and research project, Sustainable Preschool, involving around 200 teachers in Early Childhood Education. During the spring of 2022, the preschools carried out theme-oriented projects linked to sustainable development. The participating preschool teachers were then asked to carry out systematic child talks with children about learning for sustainability and their understanding of the sustainability-related content. Using content analysis, three different approaches were identified as to how teachers communicate with children systematically about various content related to sustainability: (1) joint creation of meaning, (2) question and answer, focusing on remembering facts, and (3) following the children. There is a large variation in the teachers' communicative competences. A key factor seems to be to create a shared inter-subjective atmosphere, while at the same time being open for alterity, that is, introducing new or slightly changed perspectives for the dialogue to deepen and continue.